Knowledge, attitude and practice regarding generic drugs and branded drugs: a cross sectional study - Kumar, Gyanendra; Garg, Aditi; Dhillon, Jatinder Kaur; Eranhikkal, Arshad; Smitha, Manjakandi (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Medicines play a main role in the process of human development. The rational utilization of medicines can decrease morbidity and mortality as well as improve quality of life. In an era of steeply rising health care expenses, generic medicines provide a less expensive alternative to branded medicines. Use of generic drugs can contribute to substantial savings in medicines expenditure and the issue of access and affordability is thus addressed. Methods: A sample of 500 patients selected from out patient department was randomly selected. A self-instructed questionnaire was used for the study for the duration of 1 month. Data was analyzed using IBM SPSS statistics Version 20 New York, United States. Summary statistics were expressed using mean and standard deviation (SD) for numerical variables (median and interquartile ranges [IQRs] when skewed) and counts and percentages for categorical variables. Results: Participants reported with 17.23% knowledge score, 40.65% attitude score, and 7.96% attitude score. Conclusions: In the study it was found that there is significant correlation between knowledge and attitude whereas no correlation was found between knowledge and practice regarding usage of generic drugs.